Antihyperlipidaemic and hepatoprotective activities of acidic and enzymatic hydrolysis exopolysaccharides from Pleurotus eryngii SI-04 - Chen Zhang; Juan Li; Jing Wang; Xingling Song; Jianjun Zhang; Shang Wu; Chunlong Hu; Zhiyuan Gong; Le Jia (BMC, 2017)
Abstract Background Hyperlipidaemia is the major risk factor contributing to the development and progression of atherosclerosis, fatty liver and cerebrovascular disease. Pleurotus eryngii (P. eryngii) is rich in biologically active components, especially polysaccharides that exhibit various biological activities, including reducing blood lipids. In the present study, three novel polysaccharide types, including exopolysaccharides (EPS), enzymatic EPS (EEPS) and acidic EPS (AEPS) were isolated, and the hypolipidaemic and hepatoprotective effects were investigated to better understand possible hypolipidaemic mechanisms and their hepatoprotective effects. Methods The EPS was hydrolysed by snailase (dissolved in 1% acetic acid, pH = 6) and H2SO4 (1 M) to obtain EEPS and AEPS, respectively. The in vitro antioxidant activities were measured by investigating the reducing power and the scavenging effects on radicals of hydroxyl, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and superoxide anion. The hyperlipidaemic mice were induced by perfusing a high-fat emulsion. In addition to the hepatic histopathology, the following biochemical analyses were performed to investigate the antioxidative effects, including the activities of alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT). Triacylglycerol (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), malondialdehyde (MDA) and lipid peroxidation (LPO) levels were also measured in serum and liver homogenate. Results Supplementation of EPS, EEPS and AEPS could significantly improve blood lipid levels (TC, TG, HDL-C, and LDL-C), hepatic lipid levels (TC and TG), hepatic enzyme activities (ALP, ALT, and AST) and antioxidant status (GSH-Px, SOD, T-AOC, MDA, and LPO). In addition, histopathological observations indicated that these polysaccharides had potential effects in attenuating hepatocyte damage. Conclusion These results demonstrated that both EPS and its hydrolysates EEPS and AEPS might effectively reduce serum lipid levels and protect against high-fat diet-induced hyperlipidaemia, indicating that they could be used as functional foods and natural hepatoprotectants.